Plasma native and peptidase-derivable Met-enkephalin responses to restraint stress in rats. Adaptation to repeated restraint. - Pierzchala, K (1990)
Met-enkephalin and related proenkephalin A-derived peptides circulate in plasma at picomolar concentration as free, native pentapeptide and at nanomolar concentration in cryptic forms. We have optimized conditions for measurement of immunoreactive Met-enkephalin in plasma and for generation by trypsin and carboxypeptidase B of much greater amounts of total peptidase-derivable Met-enkephalin in plasma of rats, dogs, and humans. Free Met-enkephalin (11 pM) is constituted by native pentapeptide and its sulfoxide. Characterization of plasma total Met-enkephalin derived by peptidic hydrolysis revealed a small amount (38 pM) of Met-enkephalin associated with peptides of molecular mass less than 30,000 D, and probably derived from proenkephalin A, but much larger amounts of Met-enkephalin associated with albumin (1.2 nM) and with a globulin-sized protein (2.8 nM). Thus, plasma protein precursors for peptidase-derivable Met-enkephalin differ structurally and chemically from proenkephalin A. Met-enkephalin generated from plasma by peptidic hydrolysis showed naloxone-reversible bioactivity comparable to synthetic Met-enkephalin. Prolonged exposure of adult, male rats to restraint stress produced biphasic plasma responses, with peaks occurring at 30 s and 30 min in both free native and total peptidase-derivable Met-enkephalin. Repeated daily exposure to this 30-min stress resulted in adaptive loss of responses of both forms to acute restraint. Initial plasma responses of Met-enkephalin paralleled those of epinephrine and norepinephrine, but subsequently showed divergence of response. In conclusion, Met-enkephalin circulates in several forms, some of which may be derived from proteins other than proenkephalin A, and plasma levels of both free native, and peptidase-derivable Met-enkephalin are modulated physiologically.